Analisis Spasial Kasus Pneumonia Berbasis Sistem Informasi Geografis Di Kabupaten Boyolali - Siti Slasaini Ahluljanah Ahluljanah; Sinta Novratilova; Wahyu Wijaya Widiyanto (Jurnal Manajemen Informasi dan Administrasi Kesehatan (JMIAK), 2026)
Pneumonia is a public health problem that is still a major cause of morbidity, especially in areas with diverse environmental conditions and population density, such as in Boyolali Regency. This research aims to map the distribution of pneumonia cases based on population density and regional topography and analyze the distribution pattern of pneumonia cases to support planning of targeted health interventions. The method used in this research is quantitative descriptive with a spatial analysis method based on a geographic information system. All data obtained is processed using the Qgis software application to visualize a map of pneumonia cases. The results of the Moran's autocorrelation test show a widespread pattern of case distribution with a Morans index value of -0.290, p-value 0.104 and z-score -1.0398 and there is no significant spatial autocorrelation between regions. Areas with high and medium cases are in densely populated sub-districts and in areas with relatively moderate altitude. Therefore, promotive and preventive efforts need to be carried out evenly in all regions for early anticipation in areas with a low number of pneumonia cases.